The IMPART (IMproving PAlliative care in Residential aged care using Telehealth) trial: a stepped-wedge cluster-randomised controlled trial protocol - Anita M. Y. Goh; Katrin Gerber; Kayla Lock; Ellen Gaffy; Kerry Hwang; Anna Lane; Kirsten J. Moore; Barbara Hayes; Lidia Engel; Mark Tacey; Brian Le; Paul Yates; et al. (BMC Geriatrics)
Abstract Background The quality of palliative and end-of-life care (EOLC) in residential aged care (RACFs) is variable, and often suboptimal. The aim of IMPART is to improve palliative care in RACFs. IMPART provides online training and telehealth palliative-geriatric support to aged care staff and family physicians/general practitioners (GPs) to enable timely EOLC discussions, clinical support, and improve documentation of care preferences. This may lead to preference-based care, reduction of unplanned hospitalization, and improved quality of life and EOLC. This protocol describes a study to evaluate the effectiveness, cost, and implementation process of the IMPART intervention. Methods This study is a pragmatic, stepped-wedge, cluster randomized controlled trial across 10 RACFs to evaluate the IMPART intervention. Clusters are randomly assigned to intervention or control groups. The IMPART intervention group 1) receives timely end-of-life support from specialist In-Reach teams using telehealth; 2) engages RACF staff and GPs in a Planning Ahead Team to reflect on current practices and co-design an Action Plan to improve EOLC planning and processes; 3) receives an online interactive, needs-based EOLC education program for staff and GPs working in RACFs. The control groups receive the IMPART intervention in subsequent waves. The primary outcome measure is reduction of unplanned hospital admissions and avoidable hospital transfers for residents at end-of-life when appropriate care in their RACF is possible and consistent with residents’ wishes. Secondary outcomes include reduction of emergency department presentations and length of stay of unplanned hospital admissions, and improvement in residents’ quality of life, comfort, satisfaction, and quality of EOLC. Discussion RACFs are high-mortality settings, yet the quality of palliative and EOLC varies across facilities. There is an urgent need for timely and integrated high-quality palliative care delivered in this context. Implementing IMPART, as a novel telehealth intervention, aims to address this need. This large multisite trial will provide robust evidence about the impact of the intervention (efficacy, cost-effectiveness, and process evaluation), to inform future roll-out and scale-up into the residential aged care sector. Trial registration anzctr.org.au; ACTRN12622000760774. Prospectively registered on 27/05/2022.